The wizard of oz - Dickins, Rosie; Baum, L. Frank Evangelista, Mauro (Usborne Pub Ltd London, 2010)
Faithful to L. Frank Baum's original story, this condensed version, which uses Baum's language, is a highly visual interpretation of the classic American fairy tale--a journey of colors as well as one through lands & adventures. 10" x 13". All ages